Coronary Artery Calcification, Statin Use and Long-Term Risk of Atherosclerotic Cardiovascular Disease Events (from the Multi-Ethnic Study of Atherosclerosis) - Rifai, Mahmoud Al; Blaha, Michael J.; Patel, Jaideep; Xiaoming, Jia; Cainzos-Achirica, Miguel; Greenland, Philip; Budoff, Matthew; Yeboah, Joseph; Nasir, Khurram; Al-Mallah, Mouaz H.; Virani, Salim S. (The American journal of cardiology, 2020)
The prognostic utility of coronary artery calcium (CAC) for individuals taking statins is unclear. We hypothesized that CAC remains associated with atherosclerotic cardiovascular disease (ASCVD) events in individuals using statins at baseline or among those started on statin at follow-up. The Multi-Ethnic Study of Atherosclerosis is a prospective cohort study of 6,814 participants who were enrolled between 2000 and 2002 and were free of clinical ASCVD at baseline. Four follow-up visits were conducted in 2002 to 2004, 2004 to 2006, 2005 to 2007, and 2010 to 2012. CAC was assessed at baseline and follow-up using either an electron-beam CT scanner or a multidetector CT system. Statin use at baseline and follow up was self-reported. Among 6,811 participants with complete information on statin use, mean age was 62 (SD = 10) years, 53% were women, 38% white, 12% Chinese-American, 28% African American, and 22% Hispanic. In multivariable analyses, CAC >0 was associated with a significantly higher risk of ASCVD events regardless of baseline or incident statin use. For example, hazard ratios (95% confidence interval) for the association between CAC >0 and ASCVD were 2.46 (1.41, 4.28) for baseline statin users, 2.08 (1.68, 2.57) for baseline-statin nonusers, and 2.21 (1.56, 3.15) for those started on a statin at follow-up. In conclusion, current statin use does not weaken the prognostic utility of CAC. CAC is associated with incident ASCVD regardless of baseline or incident statin use.